Supply Chain Management With An Insight Into Rosettanet - Asgari, Navid (2006)
This thesis aims at showing the role of Rosettanet standards and platform in Supply Chain management especially in a global mode. Thesis will focus at the end on management issues and implementation challenges in companies. Method of industion and an exploratory approch will be used to draw conclusions out of secondary data.